Dampak Ekonomi Ekowisata Air Terjun Suranadi Terhadap Masyarakat Lokal Di Desa Jatiluwih - Suryajaya, I Putu Agus Mahendra; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 7 No 2 (2019): VOL 7, NO 2 (2019): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i02.p16, 2019)
Tourism activity is one of process that has an important role in development of an area. One of the tourist attractions in Bali Island is Suranadi Waterfall Ecotourism Gunungsari area, Jatiluwih village. Time flies so that Suranadi Waterfall is visited by tourist. Based on the tourism situation, Suranadi waterfall ismanaged by local society through creating group. The research aims to determine of development Suranadi waterfall Ecotourism and economic impact on local society at Village Jatiluwih through several stages are Identification, Products, level of tourist visit, involvement of local society and impact on income, employment opportunities for society at Gunung Sari Umakayu area. The next stage is assessed by distributing questionnaires to local society at Gunung Sari Umakayu area, Jatiluwih village. Data collection techniques areobservation, interview, questionnaires, literature study and documentation. The techniques of determining informant Purposive Sampling. The analysis technique uses descriptive qualitative. The result of research indicates that involvement society through tourism development is at incentive participation and functional participation stages. The impact on society income after development Suranadi waterfall ecotourism, changes income, the average amount of income per month, the amount of expenditure to fulfill daily need has increased.The impact of employment opportunities after development of Jatiluwih waterfall ecotourism, amount of jobless is reduced inside and outside group, society has side job is increased that is in group only. Keywords: Impact, Socio-Economic, Ecotourism, Society